2003
DOI: 10.1111/j.1469-8749.2003.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autistic spectrum disorder in children attending mainstream schools in a Welsh education authority

Abstract: All mainstream primary schools in Cardiff were invited in July 1998 to participate in a prevalence survey of autistic spectrum disorder. Teachers of each class filled in a questionnaire based on ICD‐10 criteria for autistic disorders. The Autism Spectrum Screening Questionnaire (ASSQ) was completed on children identified with problems identified by the questionnaire. A total of 11692 children born between 1 September 1986 and 31 August 1990 were screened: 234 (2%) children were identified as requiring an ASSQ;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
(10 reference statements)
2
11
1
Order By: Relevance
“…The incidence of ASDs in this robust sample of term controls is consistent with that in the general population of Western Australia of 4 per 1000 total births (Emma Glasson, personal communication, the Western Australian Register for Autism Spectrum Disorders, 2004) and elsewhere (Webb et al 2003). It is possible that the recorded prevalence of ASD in our group of controls is somewhat higher than that seen in the general population as all controls were fully assessed by a clinical psychologist at several points in the study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The incidence of ASDs in this robust sample of term controls is consistent with that in the general population of Western Australia of 4 per 1000 total births (Emma Glasson, personal communication, the Western Australian Register for Autism Spectrum Disorders, 2004) and elsewhere (Webb et al 2003). It is possible that the recorded prevalence of ASD in our group of controls is somewhat higher than that seen in the general population as all controls were fully assessed by a clinical psychologist at several points in the study.…”
Section: Discussionsupporting
confidence: 51%
“…They include: Asperger syndrome (distinguished from autism by normal-range intellect and an absence of significant language delay), PDD-not otherwise specified (PDD-NOS), disintegrative disorder, and Rett syndrome. The prevalence of ASDs in mainstream schoolchildren has recently been estimated to be 20.2 out of every 10 000 and 25 per 10 000 if high-functioning individuals are included (Webb et al 2003).…”
mentioning
confidence: 99%
“…Active ascertainment studies such as that in a Welsh education authority have shown a minimum prevalence of 20.2 per 10 000 for children with ASD in mainstream schools; many of these children were unknown to specialist services and had unmet needs for further assessment and management. 30 Comparison of our two prevalence estimates suggests that only 74% of children with ASD were known to services (identified by any dataset). The age distribution might support the contention that this shortfall was primarily for younger and older children as prevalence across the age groups of 4-12 years was steady.…”
Section: Discussionmentioning
confidence: 91%
“…We therefore used an estimate of 2.6/10 000 for AS for subsequent calculations. A recent survey of high‐functioning PDDs in Welsh mainstream primary schools has yielded a relatively high (uncorrected) prevalence estimate of 14.5/10 000 (Webb et al. 2003, study 43) but no separate rate was available for Asperger disorder specifically.…”
Section: Prevalence Estimationsmentioning
confidence: 99%